Optimizing Treatment Selection for Early Hepatocellular Carcinoma Based on Tumor Biology, Liver Function, and Patient Status - Li X; Xu Y; Ou Y; Li H; Xu W (Journal of Hepatocellular Carcinoma)
Xing Li,1,2 Yong Xu,1,2 Yanmei Ou,1 Huikai Li,3 Wengui Xu4 1Department of Ultrasound Diagnosis and Treatment, Tianjin Cancer Hospital Airport Hospital, National Clinical Research Center for Cancer, Tianjin, People’s Republic of China; 2Department of Ultrasound Diagnosis and Treatment, Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center for Cancer, Tianjin’s Clinical Research Center for Cancer, Key Laboratory of Cancer Prevention and Therapy, Tianjin, People’s Republic of China; 3Department of Hepatobiliary Oncology, Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center for Cancer, Tianjin’s Clinical Research Center for Cancer, Key Laboratory of Cancer Prevention and Therapy, Tianjin, People’s Republic of China; 4Department of Molecular Imaging and Nuclear Medicine, Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center for Cancer, Tianjin’s Clinical Research Center for Cancer, Key Laboratory of Cancer Prevention and Therapy, Tianjin, People’s Republic of ChinaCorrespondence: Wengui Xu, Department of Molecular Imaging and Nuclear Medicine, Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center for Cancer, Tianjin’s Clinical Research Center for Cancer, Key Laboratory of Cancer Prevention and Therapy, Tianjin, People’s Republic of China, Tel +86-13820344321, Fax +86-22-23340123, Email doctorlx2023@tmu.edu.cnAbstract: Early-stage hepatocellular carcinoma (HCC) represents a critical window for curative treatment. However, treatment selection is complicated by significant heterogeneity in tumor biology, liver function, and patient performance status. This review provides a comprehensive overview of current curative-intent strategies for early-stage HCC, including liver transplantation, surgical resection, and local ablative therapies. We emphasize the importance of integrating tumor-specific characteristics-such as microvascular invasion, size, and anatomical location-with liver reserve metrics, including portal hypertension, Child-Pugh classification, and novel indices like albumin-bilirubin and albumin-indocyanine green evaluation grades. Furthermore, we discuss recent advances in non-thermal ablation techniques (eg, high-intensity focused ultrasound and irreversible electroporation), and technical innovations in radiofrequency ablation and cryoablation that are expanding the therapeutic landscape. By combining macro-level functional assessments with micro-level biological indicators, this review advocates for a personalized, evidence-based framework to optimize long-term outcomes in early HCC. The future of HCC management lies in standardizing individualized therapy.Keywords: early-stage hepatocellular carcinoma, individualized treatment, liver transplantation, resection, local ablation techniques, treatment